Microbiogeochemical Traits to Identify Nitrogen Hotspots in Permafrost Regions - Claudia Fiencke; Maija E. Marushchak; Tina Sanders; Rica Wegner; Christian Beer (Nitrogen, 2022)
Permafrost-affected tundra soils are large carbon (C) and nitrogen (N) reservoirs. However, N is largely bound in soil organic matter (SOM), and ecosystems generally have low N availability. Therefore, microbial induced N-cycling processes and N losses were considered negligible. Recent studies show that microbial N processing rates, inorganic N availability, and lateral N losses from thawing permafrost increase when vegetation cover is disturbed, resulting in reduced N uptake or increased N input from thawing permafrost. In this review, we describe currently known N hotspots, particularly bare patches in permafrost peatland or permafrost soils affected by thermokarst, and their microbiogeochemical characteristics, and present evidence for previously unrecorded N hotspots in the tundra. We summarize the current understanding of microbial N cycling processes that promote the release of the potent greenhouse gas (GHG) nitrous oxide (N2O) and the translocation of inorganic N from terrestrial into aquatic ecosystems. We suggest that certain soil characteristics and microbial traits can be used as indicators of N availability and N losses. Identifying N hotspots in permafrost soils is key to assessing the potential for N release from permafrost-affected soils under global warming, as well as the impact of increased N availability on emissions of carbon-containing GHGs.